THE LONG TRAIL: A CHIMERA-LIKE FOSSIL CRUSTACEAN INTERPRETED AS DECAPODA, STOMATOPODA, AMPHIPODA AND FINALLY ISOPODA - Pazinato, Paula G.; Haug, Carolin; Rohn, Rosemarie [UNESP]; Adami-Rodrigues, Karen; Ghilardi, Renato Pirani [UNESP]; Langer, Max Cardoso; Haug, Joachim T. (Univ Studi Milano, 2021)
The process of interpreting and evaluating a fossil is a difficult task. Isopoda is a species-rich group of peracarid eumalacostracans which represent quite a challenge when found as fossils, independent of whether we are working with fragmentary or more complete specimens. Here we describe a new fossil species of crustacean, Platuropodus odysseus n. gen. n. sp., from the Irati Formation, Permian of Parana Basin, Brazil. After misinterpretations, the fossil taxon is recognised here as a representative of Isopoda. The new species presents characters found in Phreatoicidea, Asellota and Oniscidea in a unique combination for the fossil and extant record, such as two pairs of sub-chelate anterior trunk appendages, a short region after the anus and flat uropods. This chimera-like morphology and a morphometric analysis of the sub-chelae indicate convergent evolution in the early diversification of Isopoda. The morphological diversification present in the Palaeozoic and Mesozoic fossil record of Eumalacostraca indicate a push of the past effect in different ingroups of Peracarida.
Keywords: Peracarida; Isopoda; Permian; Parana Basin; morphometric analysis; convergent evolution